Innovations and networking fostering tourist destination development in Slovakia - Gajdošík, Tomáš; Gajdošíková, Zuzanna; Maráková, Vanda; Borseková, Kamila (Quaestiones Geographicae, 2017)
The paper focuses on the implementation of innovations and networking in the sector of tourism in two Slovak mountain destinations of international significance. The main objective of the paper is to identify and evaluate how innovations and networking contribute to tourist destination development in Slovakia. The implementation of institutional innovation resulted in the establishment of formal and informal networks. The developed networks consist of representatives of all sectors co-ordinating all relevant stakeholders. Formal and informal networks and the collaboration among stakeholders have launched other types of innovations in the tourism sector. The interactions and intensity of relations among stakeholders are analysed by network analysis. Destinations are compared with the network of the same size and density through quantitative network characteristics. Based on empirical research we investigate the impact of networks and innovations on tourist destination development. Due to the synergy effect of networking and implementation of multiple innovations, tourist destination development is observed.